Christopher Robin [videorecording (Blu-Ray + DVD)] - Milne, A. A. (Alan Alexander), 1882-1956; Shepard, Ernest H. (Ernest Howard), 1879-1976 (Disney Blu-ray., 2018)
A working-class family man, Christopher Robin, encounters his childhood friend Winnie-the-Pooh, who helps him to rediscover the joys of life.